2013
DOI: 10.1007/s10689-013-9687-y
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions of ovarian cancer risk in women at increased risk for hereditary ovarian cancer

Abstract: Background: This study assessed the sociodemographic, medical and psychological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Cull et al 23 found that the best predictor of risk overestimation in a sample of women with a family history of ovarian cancer was anxiety, with their health behavior being guided by anxiety rather than objective risk. Meiser et al 24 found that women at increased genetic risk with higher levels of specific anxiety for cancer were more likely to overestimate the risk of ovarian cancer, especially if they had a mother diagnosed with the disease. Ultimately, the cited studies highlight the importance of considering anxiety as a key factor in cancer‐related risk perception and suggest the need for tailored interventions to reduce anxiety and prevent risk overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Cull et al 23 found that the best predictor of risk overestimation in a sample of women with a family history of ovarian cancer was anxiety, with their health behavior being guided by anxiety rather than objective risk. Meiser et al 24 found that women at increased genetic risk with higher levels of specific anxiety for cancer were more likely to overestimate the risk of ovarian cancer, especially if they had a mother diagnosed with the disease. Ultimately, the cited studies highlight the importance of considering anxiety as a key factor in cancer‐related risk perception and suggest the need for tailored interventions to reduce anxiety and prevent risk overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer genetic counseling is performed by a multidisciplinary team including dedicated oncologist and psychologist, according to the multistep model designed and validated within the Italian Network for “Hereditary Breast and/or Ovarian Cancer”. Structured sessions with a psycho-oncologist for psychological assessment, psychological counseling interventions and psychotherapy or emotional support are also planned for patients and their at-risk subjects [6, 9]. During the cancer genetic counseling steps devoted to information-giving and pedigree construction, anxiety and depression levels were assessed from replies to self-report questionnaire administered by the psycho-oncologist.…”
Section: Methodsmentioning
confidence: 99%